Sistema de gestión de educación continua y actualización docente de la ESPAM MFL - Castro Mendoza, Rubén Adrián (2018)
The objective of this work was to develop the Management System of Continuing Education and Teaching Update of ESPAM MFL (SIGECAD), automating the activities of the courses that are offered, such as: pre-registration, registration, course publication, registration of participation, registration of approval, certificates. For the development of the MIDAS Methodology (Interactive Methodology for the Development of Software Applications) which is divided into five phases: Definition of the System, in which the functional and non-functional requirements are defined, through a working table held with the Director and Graduate Secretary; Hypertext, the prototype of HTML5 static pages was designed; Database, the modeling of the database was performed in Microsoft SQL Server 2012; Functionality, Visual Studio 2013 Ultimate and Testing, finally corroborated the functioning of the software, which was put to the test in the teaching update 2017 for its respective validation. Positive results were obtained from the analysis of response times, which made it possible to make a comparison of how much time is taken in the process of the courses activities and systematically. Likewise, tests were carried out to measure the usability, functionality and applicability parameters, which was carried out through a survey of the teachers that were used during the training periods. Concluding that the software contributes significantly to the improvement of the processes of the activities of the courses developed by the Department of Education and Continuous Education.